Efficacy of 3D evaluation of unruptured paraclinoid aneurysms within Leksell GammaPlan® for determination of their intradural localization. (February 2023) - Ottomo, Daiki; Hayashi, Motohiro; Kawashima, Akitsugu; Yamaguchi, Koji; Okada, Yoshikazu; Kawamata, Takakazu
Highlights: Leksell GammaPlan® with the use of contrast-enhanced CISS and CTA images is helpful for preoperative 3D evaluation of paraclinoid aneurysms. Preoperative 3D evaluation of paraclinoid aneurysms within Leksell GammaPlan® provides high accuracy of their intradural localization. Preoperative 3D evaluation of paraclinoid aneurysms within Leksell GammaPlan® supports decision-making on their optimal management. Abstract: Background: Determination of the intradural unruptured paraclinoid aneurysm localization is difficult, but critical for selection of the optimal treatment strategy. Objective: To assess efficacy of the three-dimensional (3D) evaluation of unruptured paraclinoid aneurysms within Leksell GammaPlan® (LGP; Elekta AB; Stockholm, Sweden) for determination of their intradural localization. Methods: Overall, 125 incidentally diagnosed unruptured paraclinoid aneurysms in 118 patients (mean age, 55 years) underwent 3D evaluation of their localization within LGP using post-contrast thin-slice constructive interference in steady state (CISS) images, which in 41 cases were additionally co-registered and fused with the axial computed tomography angiography (CTA) source images. Results: According to the evaluation within LGP, paraclinoid aneurysms were considered intradural, transitional, and extradural in 75, 25, and 25 cases respectively. Overall, 51 of 75 aneurysms deemed to be intradural, underwent microsurgical management, and intraoperative visual inspection confirmed their intradural localization in 45 cases, whereas it was transitional in 3, and extradural in 3. If during preoperative 3D evaluation within LGP only post-contrast CISS images were used, prediction of the pure intradural localization of aneurysm was correct in 88 % of cases (95 % CI: 79–97 %), and of the pure or partial (i.e., transitional) intradural localization in 94 % of cases (95 % CI: 88–100 %), whereas it was 100 % if co-registration and fusion of the contrast-enhanced CISS and CTA source images was done. Conclusion: Intradural localization of the unruptured paraclinoid aneurysms may be effectively predicted based on their 3D evaluation within LGP using post-contrast thin-slice CISS and CTA source images, which may help with clinical decision-making.